2020
DOI: 10.5433/1679-0359.2020v41n3p753
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality and brown rot incidence in plums treated with Ascophyllum nodosum extract

Abstract: The use of extracts of algae in agriculture has been growing because of their benefits to plant development and production. The objective of this study was to evaluate the effects of Ascophyllum nodosum extract on the postharvest quality of ‘Irati’ and ‘Reubennel’ plums and on the incidence of brown rot. The treatments consisted of concentrations of 0, 0.1, 0.2, 0.3 and 0.4 mL L-1 of a commercial product containing algae extract (Algamare®) that were applied to the fruits by immersion. The fruits were then sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…These authors point out that the application at the beginning of maturation (veraison stage), which promoted the increase of anthocyanins, may be related to the phenylpropanoid route induced by higher sugar content, generating an increase in secondary metabolism, including anthocyanins and other flavonoids. Viencz et al (2020) observed an increase of phenolic compounds of 'Irati' plums, with positive linear effect according to the doses of the product containing the seaweed extract A. nodosum.…”
Section: Resultsmentioning
confidence: 88%
“…These authors point out that the application at the beginning of maturation (veraison stage), which promoted the increase of anthocyanins, may be related to the phenylpropanoid route induced by higher sugar content, generating an increase in secondary metabolism, including anthocyanins and other flavonoids. Viencz et al (2020) observed an increase of phenolic compounds of 'Irati' plums, with positive linear effect according to the doses of the product containing the seaweed extract A. nodosum.…”
Section: Resultsmentioning
confidence: 88%
“…Seaweed extract significantly increased chitinase, glucanase, peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia-lyase (PAL), and lipoxygenase enzyme activities [16][17][18]. The AnE treatment of postharvest plums increased polygalacturonase (PG) activity [180].…”
Section: Ascophyllum Nodosum Extract (Ane) Induced Defense Enzymatic ...mentioning
confidence: 99%
“…The rigorousness of Fusarium head blight, which is caused by Fusarium graminearum (Gibberella zeae), was decreased by the application of AnE to Triticum aestivum (wheat) [89]. Similarly, at a concentration of 0.4 mL/L, AnE reduced brown rot disease in the plum fruits by 50%, a disease which is caused by members of the Monilinia genus: M. fructicola, M. laxa, and M. frutigena [180]. Paiva et al [192] reported that at a concentration of 40 mL/L of AnE, the mycelia growth of the fungus Rhizopus stolonifer was significantly reduced, ultimately decreasing the incidence of soft rot by up to 22.3% in postharvest Fragaria ananassa (strawberry).…”
Section: Ascophyllum Nodosum Extract (Ane) Improves Disease Resistanc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Seaweed algae extracts are complex products, containing plant hormones, brassinosteroids, betaines, polyamines, polymers and also macro and micronutrients [11]. Although the complexity of their composition tends to make it difficult to clarify their mode of action [6,9,12], several studies have shown beneficial effects from the use of seaweed extracts for the alleviation of abiotic [13][14][15] and biotic [16,17] stresses, and in increasing crop productivity and/or product quality [18][19][20], even if they provide minute quantities of nutrients [5].…”
Section: Introductionmentioning
confidence: 99%